Effects of Hole Irrigation Device Parameters on Soil Water Characteristics Under Different Biogas Slurry Ratios - Peng Xiang; Jian Zheng; Yan Wang; You Wu (AgriEngineering, 2025)
This study investigates the impact of biogas slurry ratio, hole diameter and depth under hole irrigation on the soil wetting front migration distance and cumulative infiltration. In this study, a model describing the water transport characteristics of biogas slurry hole irrigation was developed based on the HYDRUS model. Results demonstrated that the HYDRUS model can be used for biogas slurry hole irrigation (NSE > 0.952, PBIAS ≤ ±0.34). Furthermore, the study revealed that the soil cumulative infiltration and soil wetting front migration distance decreased gradually with an increase in the biogas slurry ratio, while they increased gradually with an increase in the hole diameter and depth. The lateral and vertical wetting front migration distances exhibited a well-defined power function relationship with the soil’s stable infiltration rate and infiltration time (R2 ≥ 0.977). The soil wetting front migration distance curve can be represented by an elliptic curve equation (R2 ≥ 0.957). Additionally, there was a linear relationship between the cumulative infiltration and soil wetted body area (R2 ≥ 0.972). Soil wetting front migration distance model (<semantics>X=4.442<msubsup>f00.375</msubsup>t0.24, Z=11.988<msubsup>f00.287</msubsup>t0.124, f0=96.947<msubsup>Ks1.151</msubsup>D0.236H1.042</semantics>, NSE > 0.976, PBIAS ≤ ±0.13) and cumulative infiltration model (<semantics>I=0.3365S</semantics>, NSE > 0.982, PBIAS ≤ ±0.10) established under biogas slurry hole irrigation exhibited good reliability. This study aims to determine optimal hole diameter, depth, and irrigation volume for biogas slurry hole irrigation by establishing a model for soil wetting front migration distance and cumulative infiltration based on crop root growth patterns, thereby providing a scientific basis for its practical application.